Membangun Karakter Anak melalui Pola Asuh Demokratis: Strategi Pencegahan Bullying di Sekolah Dasar - Maria Ulfa; Wijaya, Rasman Sastra; Kosilah, Kosilah; Fadillah, Nur; Amalia, Amanda Putri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Bullying in elementary schools is often triggered by children's weak social character rooted in authoritarian or permissive parenting. This service activity aims to increase the understanding and skills of parents and teachers in implementing democratic parenting as a bullying prevention strategy in elementary schools. The implementation method includes three stages: needs analysis through surveys and interviews; education through seminars, parenting training, and teacher workshops; and evaluation and reflection based on pretest-posttest, observation, and group discussion. Results showed a significant increase in democratic parenting literacy in parents and teachers, changes in parenting behaviors that were more communicative and supportive, and a decrease in mild bullying cases in the intervention class. School and parent collaboration also succeeded in shaping a social environment that supports children's prosocial character. The implications of this activity confirm the importance of integrating democratic parenting-based character education in school programs and sustainable parenting forums as an effective preventive effort to create a safe, inclusive and empathetic learning climate.